ANALISIS MAKNA METAFORA DALAM PUISI AN DIE FREUDE KARYA FRIEDRICH SCHILLER - Jojor Putri Delima Siregar; Insenalia Sampe Roly Hutagalung; Lydia Purba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discusses the meaning of metaphors found in Friedrich Schiller's poem An die Freude. This study uses qualitative descriptive techniques to describe the types of metaphor data found. The purpose of this study is to identify and classify: the meanings of metaphors 1) structural 2) orientational and 3) ontological using Lakoff and Johnson's conceptual metaphor theory. The results show that there are 24 structural metaphor meanings, 16 orientational metaphor meanings, and 41 ontological metaphor meanings. Thus, it can be concluded that ontological metaphor meanings are the most frequently found in Friedrich Schiller's poem An die Freude.